REFORMASI PENDIDIKAN ISLAM - Syamsul Rijal (Ta`Limuna: Jurnal Pendidikan Islam, 2014)
Islamic reform movement with all its pattern, whether conservative, reformist, secular, and the fundamentalists have serious implications on the creation of educational reform. Of reform in the education sector would require a strategy and a container for the achievement of reform in Islamic education. This article investigates the weakness and lameness of Islamic education system which has been implemented is caused by several factors , such as an unpreparedness of the Islamic world in preparing the process of precipitation as an alternative system of Islamic education that is dynamic and adaptable toward the demands of the new world, and the inability of the Islamic world in reading and anticipating the world development .